Cyber-physical systems : foundations, principles and applications - Song, Houbing; Rawat, Danda B., 1977-; Jeschke, Sabina; Brecher, Christian (London : Academic Press, 2017)
Cyber-Physical Systems: Foundations, Principles and Applications explores the core system science perspective needed to design and build complex cyber-physical systems. Using Systems Science's underlying theories, such as probability theory, decision theory, game theory, organizational sociology, behavioral economics, and cognitive psychology, the book addresses foundational issues central across CPS applications, including System Design -- How to design CPS to be safe, secure, and resilient in rapidly evolving environments, System Verification -- How to develop effective metrics and methods to verify and certify large and complex CPS, Real-time Control and Adaptation -- How to achieve real-time dynamic control and behavior adaptation in a diverse environments, such as clouds and in network-challenged spaces, Manufacturing -- How to harness communication, computation, and control for developing new products, reducing product concepts to realizable designs, and producing integrated software-hardware systems at a pace far exceeding today's timeline. The book is part of the Intelligent Data-Centric Systems: Sensor-Collected Intelligence series edited by Fatos Xhafa, Technical University of Catalonia.
Part 1. Foundations -- part 2. Principles -- part 3. Applications.
Includes bibliographical references and index.
Keywords: Cooperating objects (Computer systems); Embedded computer systems; Embedded Internet devices; Cybernetics; COMPUTERS -- General; Cooperating objects (Computer systems); Cybernetics; Embedded computer systems; Embedded Internet devices; Electronic books